PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN SUMEDANG - Teddy Marliady Nurwan (JRPA - Journal of Regional Public Administration, 2020)
The research objective of the researchers was to determine the effect of human resource development on the performance of SETWAN Sumedang Regency employees and to determine the relationship of human resource development with employee performance at SETWAN Sumedang Regency.In this study researchers used the Census research method. The data collection technique was carried out through literature studies and field studies consisting of observation, and questionnaire distribution. The population in this study were all employees of ASN SETWAN, Sumedang Regency. For sampling used the Saturated Sample technique. The number of samples in this study were 37 people.Based on the test of the correlation coefficient between the development of human resources and employee performance based on the calculation of Pearson product moment correlation coefficient obtained a value of 0.798 which is in the category of a very strong relationship level. Based on the significance test it is known that the significance of the score is 0,000 <0.05, so it can be concluded that the development of human resources has an effect on the performance of employees or means significant. While the calculation of the coefficient of determination that the influence of human resource development on employee performance in SETWAN Sumedang Regency is 63.7%, while the remaining 36.3% is influenced by other factors outside the study (epsilon factor), such as Competence and Professionalism.Based on the results of the study and conclusions, then the authors advise the SETWAN perform duties according to their abilities through the development of human resource development so as to be able to shape performance well.